Comparison of Extracellular Cellulase Activities of Clostridium thermocellum LQRI and Trichoderma reesei QM9414 - Ng, Thomas K. (1981)
The crude extracellular cellulase of Clostridium thermocellum LQRI (virgin strain) was very active and solubilized microcrystalline cellulose at one-half the rate observed for the extracellular cellulase of Trichoderma reesei QM9414 (mutant strain). C. thermocellum cellulase activity differed considerably from that of T. reesei as follows: higher endoglucanase/exoglucanase activity ratio; absence of extracellular cellobiase or β-xylosidase activity; long-chain oligosaccharides instead of short-chain oligosaccharides as initial (15-min) hydrolytic products on microcrystalline cellulose; mainly cellobiose or xylobiose as long-term (24-h) hydrolysis products of Avicel and MN300 or xylan; and high activity and stability at 60 to 70°C. Under optimized reaction conditions, the kinetic properties (V(max), 0.4 μmol/min per mg of protein; energy of activation, 33 kJ; temperature coefficient, 1.8) of C. thermocellum cellulose-solubilizing activity were comparable to those reported for T. reesei, except that the dyed Avicel concentration at half-maximal velocity was twofold higher (182 μM). The cellulose-solubilizing activity of the two crude cellulases differed considerably in response to various enzyme inhibitors. Most notably, Ag(2+) and Hg(2+) effectively inhibited C. thermocellum but not T. reesei cellulase at <20 μM, whereas Ca(2+), Mg(2+), and Mn(2+) inhibited T. reesei but not C. thermocellum cellulase at >10 mM. Both enzymes were inhibited by Cu(2+) (>20 mM), Zn(2+) (>1.0 mM), and ethylene glycol-bis(β-aminoethyl ether)- N,N-tetraacetic acid (>10 mM). T. reesei but not C. thermocellum cellulose-solubilizing activity was 20% inhibited by glucose (73 mM) and cellobiose (29 mM). Both cellulases preferentially cleaved the internal glycosidic bonds of cellooligosaccharides. The overall rates of cellooligosaccharide degradation were higher for T. reesei than for C. thermocellum cellulase, except that the rates of conversion of cellohexaose to cellotriose were equivalent.